IN VITRO SCREENING OF C. ROSEUS ALKALOIDS FOR ANTIBACTERIAL ACTIVITY - S. R. VIJAYALAKSHMIDEVI; S. ANJU; G. MELCHIAS (The Bioscan, 2011)
The present work is to study the antibacterial activity of Catharanthus roseus on common human pathogens like Salmonella, Proteus, Klebsiella, Pseudomonas and Staphylococcus. This study involves extraction of active ingredients from roots of C. roseus and its antibacterial activity were tested by disc diffusion method. It is inferred that ethanol extract of the roots of C. roseus containing alkaloids has satisfactory antibacterial activity against the entire organism taken in the study, except Pseudomonas which is resistant to the alkaloids of C. roseus. Further, HPLC alkaloid profile of the C. roseus root extract has been studied. The present finding suggests that C. roseus root alkaloids can be used as antibacterial agent in new drugs for therapy against these pathogens.